Manejo de doenças em variedades tradicionais e cultivares biofortificadas de feijão-caupi [Vigna unguiculata (L) Walp] - Dias, Larisse Raquel Carvalho (2023)
The cowpea (Vigna unguiculata), has high nutritional value, and represents a basic component of the diet in the North and Northeast regions of Brazil, in addition to being part of food biofortification programs, as an alternative of food and nutritional quality for the needy populations. This culture, although rustic, is affected by several diseases, among which fungal diseases stand out. Therefore, this work aimed to develop biocontrol for the management of diseases in traditional and biofortified cultivars of cowpea. In vitro tests were performed to verify the antagonism of Bacillus methylotrophicus against Fusarium oxysporum f. sp tracheiphilum, Sclerotium rolfsii, and Macrophomina phaseolina and evaluation of the physiological and sanitary quality of traditional seeds collected from small farmers in rural communities and biofortified seeds obtained through EMBRAPA, such seeds were tested in a greenhouse, regarding the reaction to fusariosis, rot -ash stem and sclerotia wilt added or not with Bradyrhizobium sp. growth parameters and biocontrol promoted by B. methylotrophicus were also evaluated. In in vitro tests, B. methylotrophicus showed an antagonistic effect on F. oxysporum f. sp tracheiphilum, S. rolfsii, and M. phaseolina. All traditional and biofortified varieties showed high germination and emergence value in the greenhouse. The germination and emergence speed index indicated that BRS Aracê and BRS Xique-Xique were the most vigorous cultivars. In insanity tests, the highest incidence was of Aspergillus sp. and Penicillium sp., with a higher incidence in the BRS Tumucumaque variety, which is probably related to the higher water content present in this variety. Microbiolized seeds with Bradyrhizobium sp. showed an increase in plant height, number of leaves, root length, and number of nodules for Angelim and Tumucumaque varieties. The percentage of control in terms of reaction to fusariosis was more efficient in plants when co-inoculated with B. methylotrophicus and Bradyrhizobium sp. only for the variety Angelim and Aracê. The Manteguinha, BRS Tumucumaque, and BRS Xique-Xique varieties responded better to treatment with only B. methylotrophicus. Coinoculation with B. methylotrophicus and Bradyrhizobium sp. and these isolated microbiolized bacteria showed a biocontrol effect on stem gray rot and sclerotia wilt in a greenhouse. Our results indicate the potential of using B. methylotrophicus as a biocontrol and Bradyrhizobium sp. as a growth promoter, both constitute a viable and sustainable alternative for the management of fusariosis, sclerotia wilt and gray rot in cowpea production systems